Ecologia de espécies poliembriônicas com ênfase no Bioma Cerrado - Mendes-Rodrigues, Clesnan (2010)
The of more than an embryo per seed, known as polyembryony, and the asexual reproduction via seed, known as apomixis, are usually associated. The records and importance of these events have increased in the last decades both for the Angiosperms as a whole and for specific biomes, as the Cerrado, where sexual reproduction is predominant. Despite these records, information on the ecology of polyembryonic seeds is still lacking. In this scenario, we aimed to confirm polyembryony as an indicator of apomixes in woody species of Cerrado and, based on studies of embryo resource allocation, seed germination, emergency and seedling growth, try to define the advantages and disadvantages of polyembryony for the ecology of these species. Out of a 132 species sample, 30.30% presented polyembryony, although only 6.82% did have the percentage of polyembryonic seeds above 5% and were more readily associated with apomixes. Among the Melastomataceae, a characteristic Neotropical family very well represented in the Cerrado, 33.96% of the species presented polyembryony, which predominated in the tribe Miconieae. Both in the Cerrado as a whole and in the Melastomataceae in particular, the polyembryony was associated with apomixes, but in the later, the apomixes was less often associated to higher frequencies of polyembryony. More specific studies with species of Eriotheca (Malvaceae-Bombacoideae) showed mosaics of monoembryonic and polyembryonic populations in E. gracilipes and E. pubescens, with ecological differences between either types of population. Polyembryony did not affected markedly seed germinability and seedling emergence, but resulted in less homogeneous processes than the one found in monoembryonic seeds. Resource allocation studies showed that both embryo and seedling mass decreased with the number of embryos or seedling per seed. These differences reduced the survival ability of seedlings emerging from polyembryonic seeds but, on the other hand, increased the survival chances of at least one of the seedlings from these seeds (seed individual survival). In Handroanthus chrysotrichus (Bignoniaceae), some of the putative advantages of polyembryony, as allee effect and bet hedging could be experimentally evaluated. Polyembryony was clearly correlated with the occurrence of apomixis and the results presented here showed that both processes can be important factors for the persistence and distribution of plant species in the Cerrado Biome.